Analysis of the Translation of Processes in the Expository Texts of `Ask Barbara: The 100 Most Asked Questions about Love, Sex and Relationships`: A Systemic Functional Linguistics (SFL) Approach - Sodiq, Jafar; Tarjana, Sri Samiati; Nababan, M. R.; Wiratno, Tri (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This research is aimed to analyze the translation of Processes in the Expository Texts of `Ask Barbara: The 100 Most-Asked Questions about Love, Sex and Relationships`. Translation is expressing ideas in one language into another. In Systemic Functional Linguistics perspective,representation of ideas into language is part of the Ideational Meaning which focuses on the Process (verbal phrase) as the core of the clause. The SFL approach to translation studies should provide the technical terms as the linguistic evidence to account for the equivalence in the syntactical elements of the clause. The research question is: what are the Processes in the Expository Texts in Ask Barbara: `The 100 Most-Asked Questions about Love, Sex and Relationships`? The objective of this research is to find out the types of Process in the Source language (English) and those in the Target language (Indonesian). This is a descriptive qualitative study of an embedded case study type. The data source of this study is the popular book `Ask Barbara: The 100 Most-Asked Questions about Love, Sex and Relationships`. The data are the Processes in the texts. The purposive sampling technique was used to obtain the data through the content analysis and Focus Group Discussion. The technique of analyzing the data includes domain analysis, taxonomy analysis, componential analysis, and the cultural theme or values. The data analysis reveals that from 297 clauses in the target language, there are 18.8% Processes in the Thesis, 75.4% Processes in the Argument, and 11.8% Processes in the Reiteration. In each of the elements of the generic structure of the expository texts, there are 22 Relational Attributive (39.3%), 19 Material (33.9%), 11 Mental (19.6%), 2 Existential (3.5%), 1 Relational Identifying (1.8%) and 1 Verbal (1.8%) processes. The Argument part of the texts is made up of 85 Material (37.9%), 75 Relational Attributive (33.5%), 39 Mental (17.4%), 16 Verbal (7.1%), 4 Behavioral (1.8%), 3 Existential (1.3%) and 2 Relational Identifying (0.9%) processes. In the Reiteration part of the text, there are 17 Material (48.5%), 7 Mental (20.0%), 5 Relational Attributive (14.2%), 2Relational Identifying (5.7%), 2 Behavioral (5.7%), 1 Existential (2.8%) and 1 Verbal (2.8%) processes. In general, the expository texts in this book use 121 Material processes (40.7%), 102 Relational AtributiveÂ  (34.3%), 57 Mental (19.2%), 6 Existential (2%), 6 Behavioral (2%) and 5Relational Identifying (1.7%) processes. There are not many changes or shifts in the types of Process in the translation of this book. However, there are some shifts which include: 1 Material process becomes Mental process; 7 Relational:Attributive become Material processes; 3 Material processes become Relational:Attributive; 2 Material become Verbal processes; 2 Material become Existential processes; 1 Mental becomes Relational:Attributive process; 1 Relational:Attributive becomes Behavioral process and 1 Relational:Attributive becomes Mental process. Besides, there are also deletions of process in the translation because the processes are deleted or left untranslated.